Pengaruh Struktur Kepemilikan Perusahaan dan Profitabilitas Terhadap Manajemen Laba - Maya Arieska; Nurmala Nurmala; Anita Kusuma Dewi (Jurnal Ilmiah ESAI, 2023)
The study aimed to examine the effect of ownership structure and profitability on earning management. Ownership structure represented by institutional ownership and managerial ownership in focusing on mining sector companies listed in the Indonesian Stock Exchange 2017-2020 period. Earning management of dependent variable while ownership structure and profitability is independent variables. The sampling method used was purposive sampling with 18 companies during the observation period of 4 years in a row to produce a total of 72 samples and 69 for samples after data transformation. The analysis technique used in this research used SPSS 22 version with multiple linier regresision analysis. The results of this study indicate that ownership structure represented institusional ownership and managerial ownership does not effect of earning management, while profitability variable has an effect on earning management in the mining sector.